Methotrexate in the treatment of rheumatoid arthritis and psoriatic arthritis - N. V. Chichasova; A. M. Lila (Лечащий Врач)
The article provides data on the place of methotrexate in accordance with international and national recommendations 2019– 2020 in the management of patients with rheumatoid and psoriatic arthritis. Data on the prevalence of these diseases, the effectiveness and tolerability of methotrexate according to randomized controlled and cohort studies are presented. The advantages of the subcutaneous form of methotrexate in terms of efficacy and tolerability for both rheumatoid and psoriatic arthritis are discussed. Data on the tolerance of the subcutaneous form of methotrexate from various manufacturers are presented.Analysis of literature data and the results of our own research indicate the need for early prescription of methotrexate in patients with rheumatoid arthritis and patients with peripheral joint lesions in psoriatic arthritis.Numerous studies confirm the effectiveness of methotrexate in rheumatoid arthritis in relation to the symptoms of the disease, both articular and non-articular, structural damage (slowing down X-ray progression), which is accompanied by an improvement in the patient’s functional abilities. With psoriatic arthritis, methotrexate is able to reduce the activity of arthritis, enthesitis, reduce skin manifestations, and improve the functional state of the patient. Treatment with methotrexate, when the clinical effect is achieved, is accompanied by a decrease in cardiovascular complications in inflammatory lesions of the joints.